Body Balancing Control System for Quadruped Robot While Walking on Uphill and Downhill Road Using Fuzzy - Bayu, Ikrof; Zuhrie, M. Syarieffuddien (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2025)
The development of robotics in Indonesia is growing rapidly, especially in the field of robotic legs. In the Indonesian SAR robot competition there is an obstacle that is a sloping road that consists of a uphill road and downhill road. The problem with quardruped robots is the use of walking gaits that can only be used on flat fields, so they can not be used directly on sloping roads. The researchers designed a quardruped robot body balance control system using the fuzzy logic method, STM32F4 Discovery and Arduino nano as its controllers, the BNO055 IMU module as its sensor and the Dynamixel MX-28 servo for its legs. The result of this study was that the robot's time to reach a balanced body was a maximum of 1.18 seconds on a uphill road, with an equal error presentation of 2.5% roll angle and 0.95 seconds on the downhill road conditions, with a equal errors presentation of 2.2%. The test result of the high fit of the designed robot leg yielded an average error of 0.02 cm in front leg height on the uphill road, 0.02 in rear foot height when on the downhill road.